The periodontal pain paradox: Difficulty on pain assesment in dental patients (The periodontal pain paradox hypothesis) - Haryono Utomo; Indah Listiana Kriswandini; Diah Savitri Ernawati (Dental Journal (Majalah Kedokteran Gigi), 2006)
In daily dental practice, the majority of patients’ main complaints are related to pain. Most patients assume that all pains inside the oral cavity originated from the tooth. One particular case is thermal sensitivity; sometimes patients were being able to point the site of pain, although there is neither visible caries nor secondary caries in dental radiograph. In this case, gingival recession and dentin hypersensitivity are first to be treated to eliminate the pain. If these treatments failed, pain may misdiagnose as pulpal inflammation and lead to unnecessary root canal treatment. Study in pain during periodontal instrumentation of plaque-related periodontitis revealed that the majority of patients feel pain and discomfort during probing and scaling. It seems obvious because an inflammation, either acute or chronic is related to a lowered pain threshold. However, in contrast, in this case report, patient suffered from chronic gingivitis and thermal sensitivity experienced a relative pain-free sensation during probing and scaling. Lowered pain threshold which accompanied by a blunted pain perception upon periodontal instrumentation is proposed to be termed as the periodontal pain paradox. The objective of this study is to reveal the possibility of certain factors in periodontal inflammation which may involved in the periodontal pain paradox hypothesis. Patient with thermal hypersensitivity who was conducted probing and scaling, after the relative pain-free instrumentation, thermal hypersensitivity rapidly disappeared. Based on the successful periodontal treatment, it is concluded that chronic gingivitis may modulate periodontal pain perception which termed as periodontal pain paradox